2018
DOI: 10.1021/jacs.7b13488
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Chemical Reporter 6-Azido-6-deoxy-glucose Further Reveals the Substrate Promiscuity of O-GlcNAc Transferase and Catalyzes the Discovery of Intracellular Protein Modification by O-Glucose

Abstract: Metabolic chemical reporters of glycosylation in combination with bioorthogonal reactions have been known for two decades and have been used by many different research laboratories for the identification and visualization of glycoconjugates. More recently, however, they have begun to see utility for the investigation of cellular metabolism and the tolerance of biosynthetic enzymes and glycosyltransferases to different sugars. Here, we take this concept one step further by using the metabolic chemical reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
(87 reference statements)
1
52
0
Order By: Relevance
“…Furthermore, this suggests that treating cells with these MCRs will have little effect on the endogenous biosynthesis of UDP‐GlcNAc through the HBP. Finally, we tested the most recent MCRs developed by our lab: UDP‐6AzGlcNAc and UDP‐2AzGlc, which are selective for labeling O‐GlcNAc modifications, and UDP‐6AzGlc, which we recently showed might read out on intracellular O‐glucose modifications (Figure B) . In the case of UDP‐6AzGlcNAc, we saw inhibition in a similar range as UDP‐GlcNAc, thus suggesting that the 6‐azido‐6‐deoxy substitution does not interfere with binding of the UDP‐sugar to the allosteric site.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, this suggests that treating cells with these MCRs will have little effect on the endogenous biosynthesis of UDP‐GlcNAc through the HBP. Finally, we tested the most recent MCRs developed by our lab: UDP‐6AzGlcNAc and UDP‐2AzGlc, which are selective for labeling O‐GlcNAc modifications, and UDP‐6AzGlc, which we recently showed might read out on intracellular O‐glucose modifications (Figure B) . In the case of UDP‐6AzGlcNAc, we saw inhibition in a similar range as UDP‐GlcNAc, thus suggesting that the 6‐azido‐6‐deoxy substitution does not interfere with binding of the UDP‐sugar to the allosteric site.…”
Section: Methodsmentioning
confidence: 81%
“…Using synthetic sugar donors and recombinant human GFAT, we show that several of the most commonly used MCRs, modified at their 2‐ N ‐acetyl position by larger substituents (UDP‐GlcNAz, ‐GalNAz, ‐GlcNAlk, and ‐GalNAlk), do not inhibit GFAT. In contrast, placement of an azide at either the 6‐ or 2‐position of glucose (UDP‐6AzGlc and 2AzGlc) results in GFAT inhibition, and 6‐azido‐6‐deoxy‐GlcNAc (UDP‐6AzGlcNAc) might be a slightly more potent inhibitor than UDP‐GlcNAc.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cells mainly rely on aerobic glycolysis (high rates of glucose uptake and lactate production) to produce energy even in the presence of oxygen (10, 3739). Aerobic glycolysis contributes to cancer cell proliferation by providing the raw components required for to synthesis of cellular materials (40). Increasing evidences have shown that PKM2 plays a critical function in the maintenance of aerobic glycolysis, with decreased PK activity favoring cancer cell proliferation (15, 41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…A second bioorthogonal reaction step is then exploited to attached visualization or affinity tags for analysis. More recently, we and others have taken a broader approach to glycoprotein-MCR discovery through the synthesis and characterization of monosaccharide analogs that may not transit well-characterized biosynthetic pathways (Zaro et al, 2011(Zaro et al, , 2017Chuh et al, 2014Chuh et al, , 2017Li et al, 2016;Shen et al, 2017;Darabedian et al, 2018). For instance, we demonstrated that 6-azido-6-deoxy-N-acetylglucosamine (6AzGlcNAc) can bypass the traditional GlcNAc-salvage pathway to generate uridine diphosphate sugar (UDP-6AzGlcNAc) (Chuh et al, 2014), resulting in labeling of O-GlcNAcylated proteins and suggesting that cellular metabolism is more accommodating to MCRs than previously appreciated.…”
Section: Introductionmentioning
confidence: 99%